(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Karyotyping is a technique used to align the chromosomes in the decreasing order of size so that the structural and numerical changes can be easily identified. Traditional chromosome analysis is simplified by the introduction of M_FISH (multiplex fluorescence in-situ hy-bridization), a combinatorial labeling technique in which each chromosomes appears in distinct color. In this paper, Bayes classification of M-FISH chromosome images using the features intensity in five channel as well as size of the chromosome is presented. Watershed transform is employed for segmentation . Also reclassification of small misclassified segments to the neighbor region is performed as post-processing to improve the performance. The classifier was trained and tested on a set of images from the dataset [2] and an overall accuracy of 91.09% was obtained.